Analysis of a micro-scale, multi-phase device forenhanced thermal management. (29th August 2007) - Francois, M.; Shyy, W.; Chung, J.
There is a strong need to improve our current capabilities in thermal management and electronic cooling. The present study investigates an original micro-scale membrane-actuated dropwise condenser and evaporator. An actuated membrane is adopted as the droplet condensing and ejecting device. Droplets with appropriate dimensions and frequencies are formed and ejected for efficient cooling. The system design parameters and operating performances are estimated for droplet sizes ranging from 10 to 500 µm. It is demonstrated that, in this operating range, the gravity effect is small, making this device ideal for both earthbound and spacecraft applications. This paper reports the thermodynamic consideration based on a vapour?compression cycle to assess the performance of such a device, and solutions from direct numerical simulation to highlight the flow structure associated with the two-phase media.